Improving Adolescent Reproductive Health Literacy through Community-Based Health Screening and Education in Rural East Java - Teresia Retna Puspitadewi,S.Kep,Ns,M.Kes; Hilmi Yumni; Nurwening Tyas Wisnu; Hery Sumasto; Rahayu Sumaningsih; Yuni Ginarsih; Evi Yunita Nugrahini; Ira Rahayu Tiyar Sari; Ira Puspita Sari; Siswari Yuniarti; Sri Utami; Binti Yunariyah (Frontiers in Community Service and Empowerment, 2026)
Adolescents are an age group that is prone to health problems such as anemia, impaired nutritional status, premature hypertension, and the risk of metabolic disorders due to lifestyle changes. In addition, low reproductive health literacy increases the risk of risky behaviors and long-term health problems. This community service activity aims to identify adolescent health conditions through integrated screening and increase reproductive health knowledge through a community-based approach. The methods used include blood pressure, hemoglobin, hematocrit, blood glucose, Body Mass Index (BMI) measurement, and interactive counseling on reproductive health. The activity was attended by 17 teenagers from Mrican Village. The screening results showed that 17.7% of adolescents were in the prehypertensive category, 17.7% had poor nutritional status based on BMI, and 17.7% had high blood glucose levels. As many as 11.8% of adolescents had low hemoglobin levels, while 29.4% showed low hematocrit levels. Educational evaluation showed that 88.2% of participants obtained perfect scores on the reproductive health post-test.  This activity is able to provide an overview of adolescents' health conditions through health screening while increasing their knowledge about reproductive health. In addition, the findings of health risk factors in some adolescents are also an important basis for follow-up efforts in the form of health education, monitoring nutritional status, and fostering healthy living behaviors in adolescents in the community.